THE IMPLEMENTATION OF MULTICULTURAL ISLAMIC EDUCATION VALUES AT TENGGER COMMUNITY LOCAL CULTURE (An Ethnographic Study in Sapikerep Village, Sukapura, Probolinggo) - Ubaidillah Ubaidillah (Universitas Islam Malang, 2022)
This article investigates the implementation of multicultural Islamic education that exists amongst Tengger tribe kwown as indigenous community living in Sapikerep Village, Sukapura, Probolinggo Regency, East-Java. The purposes of this article are; first, describe, analyze and interpret the values of multicultural Islamic education contained in the local culture, second, describe, analyze and interpret the application of multicultural Islamic educational values in the local culture of the Tengger people in Sapikerep Village, Sukapura, Probolinggo Regency. This research is a type of qualitative research with Cresswell's realist ethnographic approach. Data collection techniques use participant observation techniques, in-depth interviews, and documentation. While informant determination use purposive and snowball sampling techniques. As for analyzing data use spreadly analysis techniques, which perform analysis with four steps, namely domain analysis, taxonomic analysis, component analysis, and cultural theme analysis. The continuation of data validity test techniques using source trianggulation techniques, methods, and theories. The results of this study show there are values of Multicultural Islamic education tengger culture in Sapikerep in the form of respect, mutual advice, help each other and Ã‚Â conserve nature/environment. These values are implemented in tengger ceremonies, such as Kasada ceremonies, Karo ceremonies, Unan-Unan and others. By the end, formed the implementation of multicultural Islamic educational values to the local culture of the Tengger tribe in the form of AGIL -based assimilation models (adaptation, goal attainment, integrating, and latency).Keywords:Ã‚Â Values of Multicultural Islamic Education, Tengger local culture